Recovery Over Time and Prognostic Factors in Treated Patients with Post-Infectious Olfactory Dysfunction: A Retrospective Study. (October 2020) - Ogawa, Takao; Nakamura, Keigo; Yamamoto, Sayuri; Tojima, Ichiro; Shimizu, Takeshi
Objectives: The aims of the present study were to clarify the time-course of olfactory recovery and the prognostic factors in PIOD patients treated with Toki-shakuyaku-san (TSS). Methods: A retrospective cohort study of patients with PIOD was conducted by reviewing patients' medical records. This study included patients who received TSS or a combination of TSS and zinc sulfate. Olfactory function was examined by T&T olfactometer at each 3-monthly follow-up visit. Patients with normal and mild olfactory dysfunction were excluded. Gender, age, treatment, duration of disease until the first visit and olfactory function scores of the T&T olfactometer at the first visit were analyzed as candidate clinical predictors of recovery. Results: A total of 82 PIOD patients with ages ranging from 16 to 79 years were included. The mean duration of follow-up was 14.5 months (range 3-45 months). The number of patients with olfactory recovery increased for 24 months and the cumulative recovery rate was 77.3%. In about 60% of patients, olfactory recovery occurred within 6 months. Multivariate analysis showed that younger age (<65 years) and residual olfactory function were significantly associated with good olfactory recovery. Conclusions: We revealed recovery rates over time in patients with PIOD. The recovery of olfactory function often occurred during the early period (≤6 months). However, the number of patients with olfactory recovery increased for a long-term of 24 months after the first visit. Residual olfactory function and younger age were prognostic factors exactly. TSS may be a useful therapeutic agent for patients with PIOD. We believe that these results provide important information that is useful for counseling patients with PIOD.